(untitled) - Streetman, Ben G. (Boston, 2016)
Solid State Electronic Devices is intended for undergraduate electrical engineering students or for practicing engineers and scientists interested in updating their understanding of modern electronics
Keywords: Chất bán dẫn,Semiconductors